Perbandingan Kurikulum Pendidikan Vokasional Agribisnis di Berbagai Institusi Pendidikan - Edi Sulaiman; Suci Amalia; Muhammad Diki Ariansyah; Sa’idy (CV. Creative Tugu Pena, 2022)
The vocational agribusiness education curriculum plays a crucial role in producing skilled workers ready to face the challenges of a modern and dynamic agricultural sector. However, there are significant differences among educational institutions in terms of curriculum development, implementation, and its alignment with the needs of the business and industrial sectors (DUDI). This study aims to compare the vocational agribusiness education curricula of five different institutions in 2022 and to analyze the extent to which curriculum structure, learning approaches, soft skills enhancement, relevance to DUDI, and technology integration are applied. This research employed a descriptive qualitative approach using a comparative study method. Data were collected through document analysis, interviews, and observations at five institutions: Universitas Doktor Husni Ingratubun Papua, Universitas Nahdlatul Ulama Kalimantan Selatan, Universitas Galuh, Universitas Brawijaya, and Sekolah Tinggi Ilmu Pertanian Mujahidin Toli-Toli. Data were analyzed thematically through the processes of data reduction, data display, and conclusion drawing. The results indicate that the curricula of Universitas Brawijaya and Universitas Galuh are more structured and competency-based compared to the others. Project-based learning and teaching factory approaches have been introduced but are not yet evenly implemented. Technology integration remains limited, while soft skills development is not yet a central focus. Additionally, relevance to DUDI is stronger in institutions with active partnerships. This study recommends the standardization of a nationally competency-based curriculum, strengthening collaboration with DUDI, and enhancing technology and soft skills integration in vocational agribusiness education